The First Report of a Missense Variant in RFX2 Causing Non-Syndromic Tooth Agenesis in a Consanguineous Pakistani Family - Khan, Sher Alam; Khan, Saadullah; Muhammad, Noor; Rehman, Zia Ur; Khan, Muhammad Adnan; Nasir, Abdul; Kalsoom, Umm-e-; Khan, Anwar Kamal; Khan, Hassan; Wasif, Naveed (Frontiers in Genetics, 2022)
Abstract Background The syndromic and non-syndromic congenital missing teeth phenotype is termed tooth agenesis. Since tooth agenesis is a heterogeneous disorder hence, the patients show diverse absent teeth phenotypes. Thus identifying novel genes involved in the morphogenesis of ectodermal appendages, including teeth, paves the way for establishing signaling pathways. Methods and Results We have recruited an autosomal recessive non-syndromic tooth agenesis family with two affected members. The exome sequencing technology identified a novel missense sequence variant c.1421T>C; p.(Ile474Thr) in a regulatory factor X (RFX) family member (RFX2, OMIM: 142765). During the data analysis eight rare variants on various chromosomal locations were identified, but the co-segregation analysis using Sanger sequencing confirmed the segregation of only two variants RFX2: c.1421T>C; p.(Ile474Thr), DOHH: c.109C>G; p.(Pro37Ala) lying in a common 7.1MB region of homozygosity on chromosome 19p13.3. Furthermore, the online protein prediction algorithms and protein modeling analysis verified the RFX2 variant as a damaging genetic alteration and ACMG pathogenicity criteria classified it as likely pathogenic. On the other hand, the DOHH variant showed benign outcomes. Conclusion RFX2 regulates the Hedgehog and fibroblast growth factor signaling pathways, which are involved in the epithelial and mesenchymal interactions during tooth development. Prior animal model studies have confirmed the expression of rfx2 at a developmental stage governing mouth formation. Moreover, its regulatory role and close association with ciliary and non-ciliary genes causing various dental malformations makes it a potential candidate gene for tooth agenesis phenotype. Further studies will contribute to exploring the direct role of RFX2 in human tooth development.